Online Method And Mental Lexicon In Children Language Processing Psycholinguistics Approach - Karinda Karinda; Andi Asrifan; Sam Hermansyah; Buhari Buhari (La Ogi : English Language Journal, 2022)
The objectives of the research are to describe the types of directive speech acts of the teacher and student in learning and explain a pragmatic meaning of directive speech acts in the interaction of teacher and student in class XI MIPA 2 Pondok Pesantren Al-Urwatul Wutsqaa Benteng year of 2020/2021. This research method was a qualitative descriptive method with the purpose of getting an objective description of the teacher and student speech in the interaction of teaching and learning in class XI MIPA 2 Pondok Pesantren Al-Urwatul Wutsqaa Benteng. Data collection techniques usedin this study were uninvolved conversation techniques, recording techniques, and note-taking techniques. The data collection technique was used by researcher togain complete data regarding the types of directive speech acts.The researcher carried out the analysis includes four phases: identification, classification, interpretation, and report. Data gained in this study amounted to 16 speeches. There were 4types ofdirective speech acts from 16 speeches: types of directive speech acts questions, command, request, and prohibition. The pragmatic meaning found as follows: sense ofreminding, directing, commanding, pleading, recommending, and criticizing.